2013
DOI: 10.4236/fns.2013.411a001
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a<i> Lactobacillus</i>-Based Probiotic for the Control of Necrotic Enteritis in Broilers

Abstract: Necrotic Enteritis (NE) caused by Clostridium perfringens (CP) in poultry is probably the most important bacterial disease in terms of economic implications. The disease is multi-factorial and is invariably associated with predisposing factors. The present study investigated the effect of a commercially available Lactobacillus-based probiotic (FM-B11) for the control of necrotic enteritis in broiler chickens. In experiment 1, one-day-of-hatch broiler chicks were randomly allocated to the following treatment gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…This strain was able persist in the chicks for the duration of the experiment, caused a reduced colonization by C. perfringens after 15 days, although no direct anti- C. perfringens activity was evident in vitro (La Ragione et al, 2004 ). Layton and colleagues tested the efficacy of the probiotic FloraMax-B11 (FM-B11), which consists of several LAB strains (Table 1 ) on chicks challenged with E. maxima, S. typhimurium and C. perfringens (Layton et al, 2013 ). The chicks started receiving the probiotic on day 14 and were infected 7 days later.…”
Section: Feeding “Live” Bacteria and Yeastsmentioning
confidence: 99%
See 1 more Smart Citation
“…This strain was able persist in the chicks for the duration of the experiment, caused a reduced colonization by C. perfringens after 15 days, although no direct anti- C. perfringens activity was evident in vitro (La Ragione et al, 2004 ). Layton and colleagues tested the efficacy of the probiotic FloraMax-B11 (FM-B11), which consists of several LAB strains (Table 1 ) on chicks challenged with E. maxima, S. typhimurium and C. perfringens (Layton et al, 2013 ). The chicks started receiving the probiotic on day 14 and were infected 7 days later.…”
Section: Feeding “Live” Bacteria and Yeastsmentioning
confidence: 99%
“…After 10 days, they observed a high reduction of mortality in the group treated with FM-B11, along with reduced intestinal lesions and C. perfringens counts. Furthermore, FM-B11 was shown to be active against C. perfringens in vitro (Layton et al, 2013 ). Allaart et al ( 2011 ) described an example of an antagonistic action that targeted pathogenicity via the inhibition of toxin production.…”
Section: Feeding “Live” Bacteria and Yeastsmentioning
confidence: 99%
“…In poultry, yeast as a probiotic has more effect of improving the performance of birds. Saccharomyces cerevisiae, obtained from intestine of poultry, functions as an effective probiotic for prevention of NE (Layton et al 2013). Priya and Babu (2013) showed that Saccharomyces cerevisiae supplementation had a positive effect on the morphology of intestine.…”
Section: Yeast As Probiotics For Prevention Against Snementioning
confidence: 99%
“…Many studies have demonstrated that potentially probiotic strains of bacteria and competitive exclusion cultures reduce the incidence of NE (e.g. Elwinger et al, 1992;La Ragione et al, 2004;Layton et al, 2013;Tactacan et al, 2013). These microbial interactions are protective rather than predisposing but there are examples of bacterial infections that have been found to predispose to greater NE development; for example, early infection with a Salmonella enterica serovar Typhimurium isolate increased NE-related mortality and lesion scores, perhaps resulting from a change in host immune response (Shivaramaiah et al, 2011).…”
Section: Disruption Of Microbiotamentioning
confidence: 99%